Phase transitions in 1-bromoadamantane compared to 1-chloroadamantane: similarities and unique features. Issue 40 (11th October 2021) - Danilov, Igor V.; Gromnitskaya, Elena L.; Brazhkin, Vadim V.
Abstract : Our ultrasonic studies have detected for the first time the λ-anomaly of the elastic properties and have confirmed that the phase transition in 1-bromoadamantane is a weak first-order having some properties of a second-order phase transition. Abstract : The elastic properties of 1-chloroadamantane and 1-Bromoadamantane in order–disorder and order–quasi-order phase transitions at temperatures in the range of 77–305 K and high pressures up to 1.1 GPa are studied by the ultrasonic method. The elastic moduli of halogenated adamantanes clearly indicate these transitions, demonstrating high capabilities of the ultrasonic method. Our ultrasonic studies have detected for the first time the λ-anomaly of the elastic properties and, thereby, have confirmed that the phase transition from the orientationally ordered to quasi-ordered phase (M → O) in 1-bromoadamantane is a weak first-order phase transition having some properties of a second-order phase transition. The pressure derivatives of the elastic moduli of 1-chloroadamantane and 1-bromoadamantane in the orientationally ordered phase at 77 K are d B /d P ≈ 8, which allows using the Lennard-Jones potential to theoretically describe this phase.